Cooling Tower Performance Efficiency in Water Treatment Unit at PT. X Sukowati - Nurrahman, Arif; Zami Furqon; Farid Alfalaki Hamid; Muhammad Iqbal Al Haritsah (Jurnal Ilmiah Teknik Kimia, 2024)
PT X Sukowati is one of the oil and gas industries that operates in the upstream sector, precisely in the oil and gas production process. The purpose of the research is to evaluate the efficiency of the Cooling Tower at PT X Sukowati, and whether it is still feasible to use in the process of cooling the engine to the poorboy and compressor. The research method used is qualitative because this method includes observation, literature study, interviews, and field orientation to obtain data related to the efficiency performance process of the Cooling Tower. Then the analysis is carried out by comparing the design data with the operating conditions of the Cooling Tower. The Cooling Tower works using the counter flow principle of water entering the water flow outlet, sprinkled with a nozzle from a sprinkle head that rotates above the PVC filler. The problem that often occurs in the Cooling Tower is the growth of moss in the cooling water pond. This is maintained by giving algae as much as 600 ml per day to the cooling water pond. The average efficiency value obtained at the Cooling Tower is 59.12%. This result shows that the Cooling Tower can still function properly. The efficiency value is better than the design data efficiency of 50%.